CCNP ROUTE portable command guide - Empson, Scott (Cisco Press, 2010)
CCNP ROUTE Portable Command Guide All the ROUTE 642-902 Commands in One Compact, Portable Resource Scott Empson Hans Roth Preparing for the CCNP ® exam? Working as a network professional? Here are all the CCNP-level commands for the Implementing Cisco IP Routing (ROUTE) exam you need in one handy resource. The CCNP ROUTE Portable Command Guide is filled with valuable, easy-to-access information and is portable enough for use whether you're in the server room or the equipment closet. This book helps you memorize commands and concepts as you work to pass the CCNP ROUTE exam (642-902). The guide summarizes all CCNP certification-level Cisco IOS ® Software commands, keywords, command arguments, and associated prompts, providing you with tips and examples of how to apply the commands to real-world scenarios. Configuration examples throughout the book provide you with a better understanding of how these commands are used in simple network designs. Use CCNP ROUTE Portable Command Guide as a quick, offline resource for research and solutions. --Logical "how-to" topic groupings inside the front and back covers provide one-stop research --Compact size makes it easy to carry with you, wherever you go --Helps you review important commands before taking the CCNP ROUTE certification exam --"Create Your Own Journal" appendix with blank, lined pages enables you to personalize the book for your own needs This book is part of the Cisco Press ® Certification Self-Study Product Family, which offers readers a self-paced study routine for Cisco certification exams. Titles in the Cisco Press Certification Self-Study Product Family are part of a recommended learning program from Cisco Systems ® that includes simulation and hands-on training from authorized Cisco Learning Partners and self-study products from Cisco Press.
Print version record
Keywords: Routers (Computer networks) -- Study guides -- Examinations; Routing protocols (Computer network protocols) -- Study guides -- Examinations; Internetworking (Telecommunication) -- Study guides -- Examinations; Telecommunications engineers -- Study guides -- Certification -- Examinations; Routeurs (Réseaux d'ordinateurs); Examens; Guides de l'étudiant; Protocoles de routage (Protocoles de réseaux d'ordinateurs); Examens; Guides de l'étudiant; Interconnexion de réseaux (Télécommunications); Examens; Guides de l'étudiant; Internetworking (Telecommunication); Examinations; Routers (Computer networks); Examinations; Telecommunications engineers; Certification; Examinations; Study guides